Pendekatan Manajemen Peserta Didik pada SD IT Al-Hijrah 2 Laut Dendang - Fitri Amalia Harahap; Adelia Fitri; Aidatul Fauziah; Rizka Akmalia; Ibnu Qital Pasaribu (Journal on Education, 2023)
This article aims to find out and analyze the student management approach that exists at SD IT Al-Hijrah 2 Laut Dendang school. This article contains three student management approaches that are used, namely the first, quantitative approach (the quantitative approach) is this approach that focuses more on administrative and bureaucratic aspects contained in educational institutions. Both qualitative approaches (the qualitative approach) are aimed at making students capable, this approach aims to make students happy and prosperous. The third, integrated approach is this approach is a combination of the two approaches above, in this approach students are asked to fulfill bureaucratic and administrative demands at school and schools also offer other incentives that can meet the needs and welfare of students.